Species of Hexabothriidae (Monogenea) may have extensive distribution ranges reflecting multiple host species: evidence from three new South African records - Vaughan, David B.; Christison, Kevin W.; Hansen, Haakon; Bullard, Stephen A. (Zootaxa, 2023)
Many hexabothriid genera require renewed taxonomic attention to provide additional detailed comparative data from new material to resolve existing species quandaries. Our current study describes and provides additional museum material for three hexabothriid species from three genera from South Africa: Erpocotyle catenulata (Guberlet), which is confirmed as a valid species, Heteronchocotyle gymnurae Neifar, Euzet and Ben Hassine, and Hypanocotyle bullardi Chero, Cruces, Sáez, Carolina, Camargo, Portes Santos and Luque. Evidence of these three hexabothriid species from South Africa suggests that hexabothriids have more globally widespread distributions, and that they are less host-specific than previously considered. A detailed summary of hexabothriids reported from the triakid hosts, Galeorhinus galeus and Mustelus mustelus is provided, and the host-specificity of hexabothriids is discussed.